2018
DOI: 10.4274/tjo.56750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Biomechanical Changes After Collagen Crosslinking in Patients with Progressive Keratoconus by Ocular Response Analyzer

Abstract: Objectives:To evaluate corneal biomechanics before and after collagen crosslinking (CXL) in patients with progressive keratoconus.Materials and Methods:In this prospective study, CXL was performed under topical anesthesia after removal of the epithelium (epi-off technique) by applying ultraviolet A (UVA) light at a wavelength of 365 nm and power of 3 mW/cm2 or 5.4 joule/cm2. Isoosmolar 0.1% riboflavin solution was administered before and during UVA irradiation. In addition to ophthalmologic examination, ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“… 36 , 37 In another study evaluating biomechanical changes with ORA before and after CXL, p2area, which is the most valuable predictive parameter in progression, was reported to be the parameter that best demonstrates biomechanical changes after CXL, but there was no significant change in CRF and CH values. 38 In a study by Küçümen et al 39 examining changes in CRF and CH after CXL, no statistically significant change was observed in CH in the early or late postoperative period, while the change in CRF showed early significance that disappeared in the late postoperative period.…”
Section: Discussionmentioning
confidence: 97%
“… 36 , 37 In another study evaluating biomechanical changes with ORA before and after CXL, p2area, which is the most valuable predictive parameter in progression, was reported to be the parameter that best demonstrates biomechanical changes after CXL, but there was no significant change in CRF and CH values. 38 In a study by Küçümen et al 39 examining changes in CRF and CH after CXL, no statistically significant change was observed in CH in the early or late postoperative period, while the change in CRF showed early significance that disappeared in the late postoperative period.…”
Section: Discussionmentioning
confidence: 97%
“…Another limitation of this study is that when we simulate ORA measurements, we calculated CH and CRF according to Eq (5) and (6), which may be not the real relation of ORA parameters and P 1 , P 2 . While the relationship has not been determined at present, researches have reported that experimental CH and CRF are linear positive correlation with the calculated CH and CRF [29] and our aim was to find the correlation between ORA parameters and corneal biomechanical parameters qualitatively. Therefore, it is feasible to calculate CH and CRF by Eq (5) and (6).…”
Section: Discussionmentioning
confidence: 98%
“…As corneal topography is measured at a specific intraocular pressure IOP and is distinct from the unloaded shape that would be obtained at an IOP of 0 mm Hg, the undeformed state was solved by a custom finite element model at first. The variation of central corneal coordinate along the air-puff force during the measurements was extracted (Figure 3(b)) to get the two applanation pressures ( P 1 and P 2 ) and ORA parameters (CH and CRF) were calculated according to the following equations [29]:T17CH=P1P2CRF=P10.7P2…”
Section: Methodsmentioning
confidence: 99%
“…B12) and the UVA undergo a photochemical reaction with environmental oxygen and generate free oxygen radicals. This reaction is responsible for the formation of additional covalent bonds between the collagen fibrils in the stroma with the result of reinforcing the structure of corneal stroma influencing its biomechanical function [19]. The literature reports few data about the possible modification of mechanical behaviour of corneal tissue due the induced injury and also due to the treatment of the lesion with the riboflavin/UV-A corneal phototherapy.…”
Section: Introductionmentioning
confidence: 99%